“Motherhood forced me to cope with my disability”: identity intersection among mothers with physical disabilities - Shpigelman, Carmit-Noa; Karlinski Argi, Limor (Frontiers in Psychology, 2024)
Background Although motherhood plays a meaningful role in the formation of a woman’s identity, most studies have focused on the process of identity transformation in the transition to motherhood among non-disabled women; less is known about this process among women with physical disabilities who become mothers. Objective The present study aimed to understand and describe the subjective experiences of Israeli women with lifelong physical disabilities in their motherhood journey from the perspective of the intersection of their motherhood and disability identities, and from the disability studies approach. Methods Semi-structured interviews were conducted with 20 Israeli mothers with visible lifelong physical disabilities who live in the community and raise their children. Results Three themes emerged from the interviews: (1) the decision to become a mother: Coping with the disability identity for the first time; (2) The FIRST 3 years: Depending on others as limiting their motherhood identity; (3) after age three: Balancing the motherhood and disability identities. Conclusion The transition to motherhood led to identity transformation among women with physical disabilities. Becoming a mother increased the tension between dependence and independence in the context of disability, which also influenced the intersection of their motherhood and disability identities and their wellbeing. Practitioners should provide emotional support to mothers with disabilities and help them embrace the positive aspects of each identity and strike a balance between them.